Estranhamento como nexo causal do adoecimento docente na Universidade Federal de Uberlândia - Forattini, Cristina Damm (2017)
The thesis here defended seeks do affirm that the defamiliarization is the causal link of illness at teaching work in the federal public higher education, in other words, the illness at work of teacher is directly related to the defamiliarization condition. It was assumed that the precariousness of the teaching work create factors that causes physical and psychic suffering transmuted into diseases that present themselves in the life of the teaching worker. It was noted that the defamiliarization is identified as a factor of submission to the precarious conditions of the higher magisterium. Human de-activism is intensified by public policies, bureaucracy, and productivism. Otherwise the lack of work structure, the aridity of the individualistic environment and the dehumanization of relationships with their peers and students sickens, systematically, the lecturer. The physical and psychological load of work outweigh the bearable leading to stress, depression and emotion exhaustion. They are excluded of generic life, rest hours, leisure and family life, working at home, in the early hours and weekends. The empirical research was developed based on the Federal University of Uberlândia study case methodology. It occurred in the areas of knowledge of the Humanities and Applied Social Sciences because they are interconnected areas, that dialogue, interdisciplinary and centered on the historical, social and active human being. As the participants were heard, in semi-structured interviews, teachers with teaching time equal to or greater than 8 (eight) years, considering that this time is enough to have experienced two higher managements, including university expansion. The participants have a doctoral degree and work in stricto sensu undergraduate and postgraduate education, in extension and research projects, and in administrative functions, based in the Campus Umuarama or Campus Santa Mônica.